Research on PLM – Based Cost Estimation of Automotive Parts - Tukhtarov Nodir Normurodovich; Turanov Maruf Gapporovich; Juraeva Gulchehra Shodievna (Genius Journals, 2022)
Faced with the fierce market competition, automotive parts enterprises should make a quick and accurate cost estimation of automotive parts so as to provide basis for decision making. It discusses the importance of quick and accurate cost estimation of automotive parts, and analyses the method of estimation of automotive parts. A product configuration and cost estimation model based on PLM system is offered. Meanwhile, a optimization model of cost estimation based on MATLAB and a case study base on the optimization model are made after that
Keywords: optimization; estimation; MATLAB; Automotive parts; Product data management